التطور في دراسة الأناجيل الأربعة وأثره في مفهوم العقائد المسيحية: عقيدة صلب المسيح وقيامته: The development in the study of the four Gospels and its impact on the concept of Christian doctrines: the doctrine of the crucifixion and resurrection of Christ - Mohamed Selima, Zaher Hamed Zaher; Mohd. Daud, Noor Amali (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يتناول البحث النظريات التي تدور حول نشأة الأناجيل منذ العهد المسيحي الأول إلى أن تبلورت في صورة الكتاب المقدس الحالي (الأناجيل الأربعة)، وتكمن إشكالية البحث في الاختلاف بين النظريات الإنجيلية التي طُرحت لمعرفة المصدر الذي اعتمدت عليها الأناجيل في كتابتها، فهي متشابهة في كثير من موادها وترتيبها خاصة (متى ومرقس ولوقا) والتي تعرف بالأناجيل الإزائية، لذلك هدفت الدراسة إلى النظر في المشكلة الإزائية المتعلقة بالأناجيل الثلاثة وطبيعتها وتفسيرها والتعريف بالنظريات الإنجيلية التي ذكرها العلماء والمؤرخون في مصادر تلك الأناجيل. وقد اعتمد الباحث المنهج الاستقرائي والمنهج الوصفي في تتبع نصوص العهد الجديد وآراء العلماء، ثم المنهج التحليلي للنصوص والوقائع التاريخية، كما اعتمد المنهج النقدي في نقد آراء بعض علماء النصاري من خلال الدراسات النقدية للأناجيل. وخلصت النتائج إلى أن الأناجيل الحالية ليست هي الإنجيل المنزل، وإن صحت بعض الأقوال التي جاءت فيها، وأن إنجيل المسيح التي توصل إليها العلماء من خلال الوثيقة "Q" وندوة يسوع هو أقرب إنجيل للإنجيل المنزل على المسيح، حيث لم يُذكر فيه قصة الصلب والقيامة، مما يبطل أهم العقائد النصرانية التي تعتنقها الكنيسة اليوم. ABSTRACT The research deals with the theories that revolve around the origin of the Gospels from the early Christian era until they crystallized into the current form of the Bible (the four Gospels). The problem of the research lies in the difference between the Gospel theories that were put forward to know the source on which the Gospels relied in writing them. They are similar in many of their materials and their arrangement, especially (Matthew, Mark and Luke), which are known as the Synoptic Gospels. Therefore, the study aimed to examine the synoptic problem related to the three Gospels, its nature and interpretation, and to introduce the Gospel theories mentioned by scholars and historians in the sources of those Gospels. The researcher adopted the inductive and descriptive methods in tracing the texts of the New Testament and the opinions of scholars, then the analytical method for texts and historical facts, and he also adopted the critical method in critiquing the opinions of some Christian scholars through critical studies of the Gospels. The results concluded that the current Gospels are not the revealed Gospel, even if some of the statements contained therein are true, and that the Gospel of Christ that scholars arrived at through document "Q" and the Jesus Symposium is the closest Gospel to the Gospel revealed to Christ, as it does not mention the story of the crucifixion and resurrection, which invalidates the most important Christian doctrines that the Church adheres to today.